The Consequences of Adolescent Pregnancy: A Social, Medical, and Psychological Analysis - Bednarz, Karolina; Basiaga, Bartosz; Żądecka-Kobiałka, Klaudia; Putra, Anna; Marchaj, Magdalena; Nowicka-Jasińska, Monika; Frączyk, Paweł; Bieniek-Zając, Sara; Baczkowski, Sebastian; Krawiec, Klaudia (Journal of Education, Health and Sport, 2024)
Introduction: Adolescent pregnancy remains a contentious issue despite improvements in quality of life and increased access to sexual education. The average age of first pregnancy has shifted due to financial instability among young people, leading to delayed pregnancies until financial stability is achieved. Teenage mothers face social stigma, and early sexual initiation not only increases the risk of pregnancy but also sexually transmitted infections (STIs). Often, adolescent pregnancies are unwanted, resulting in delayed medical consultation due to fear or ignorance. Aim of the Study: This study aims to investigate the medical and social implications of adolescent pregnancy, emphasizing the importance of early sexual education and comprehensive healthcare support. Description of the State of Knowledge: Adolescent pregnancy, defined as pregnancy between ages 10 and 19, is a global concern with millions of cases annually. It poses significant health risks, including premature birth, low birth weight, and intrauterine growth restriction. Socially, it affects educational attainment and financial stability, with adolescents from lower socioeconomic backgrounds facing greater challenges. Early sexual initiation and risky sexual behaviors further compound the issue, increasing the risk of STIs. Lack of comprehensive sexual education exacerbates these risks, highlighting the need for multidisciplinary support from healthcare professionals. Conclusions: Adolescent pregnancy requires a holistic approach encompassing medical, social, and legal dimensions. Effective sexual education programs, involving gynecologists, pediatricians, and educators, are essential for prevention. Legal frameworks must protect adolescents and address issues of consent and sexual health. Additionally, access to comprehensive healthcare services, including prenatal care and contraception, is crucial for mitigating the adverse effects of adolescent pregnancy on both individuals and society.